Maintenance Of Local Languages Through Assistance Of Local Content Teachers In Elementary School - Yunie Amalia Rakhmyta (Penerbit Widina, Widina Media Utama, 2022)
Â One of the opportunities to strengthen the resilience of local languages is through local content subjects. The unavailability of reference standards in developing local content curricula in primary schools confuses teachers in projecting the targets to be achieved. The unavailability of the competency standard formulation has caused the field of study of local content to differ from one elementary school to another. Currently, the field of study of local content is taught by teachers who do not have special qualifications. Some teachers are appointed with religious education, sports education, art education. With this background, teachers often do not have references to representative local languages have not mastered the rules of local languages well. Under these conditions, training and mentoring efforts are needed. This service activity is carried out with a strategy starting with need assessment, FGD, curriculum formulation, teacher assistance, and monitoring and evaluation. This service aims to awaken teacher and student awareness about the importance of maintaining local languages and references in learning local content in the form of draft teaching materials.Â